Evaluation of the Safety of Rapid Parenteral Nutrition Titration. Issue 3 (12th June 2019) - Curry, Dominick; Giancarelli, Amanda; Vickers, Donald C.
Abstract: Background: Initiation of parenteral nutrition (PN) can cause complications including hyperglycemia (HGL), electrolyte abnormalities, and refeeding syndrome (RFS). These concerns lead many to titrate over several days, but our practice is to titrate PN to goal within 8 hours. The aim of this study was to evaluate the safety of titrating PN to goal within 8 hours. Methods: This was a single‐center, retrospective study of adult patients initiated on continuous PN with titration to goal rate in <8 hours. The primary composite outcome included the incidence of HGL, hypomagnesemia, hypophosphatemia, or hypokalemia within 24 hours of PN initiation. Secondary outcomes included analyses of patients with risk factors for HGL and RFS, critically ill patients, and individual components of the composite outcome. Results: Three hundred forty‐two patients were included, with a primary outcome incidence of 24.6% (HGL 17.4%; hypokalemia 1.8%; hypomagnesemia 0.6%; hypophosphatemia 8.5%). The primary outcome was more common in the HGL group (34.3% vs 14.7%, P < 0.01) and in the ICU group (40.9% vs 20.7%, P < 0.01). Mean 24‐hour blood glucose > 180 mg/dL occurred more in the HGL group (27.9% vs 7.6%, P < 0.01) and in the ICU group (34.8% vs 13.8%, P < 0.01). In patients with no risk factors, the primary outcome was 11.9%. Conclusion: Rapid PN titration was likely safe in patients without risk factors for HGL or RFS. Further evaluation of protocolized HGL management is needed to determine the risk of HGL in patients with HGL risk factors.